2010
DOI: 10.1111/j.1558-5646.2010.01137.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive Frequency-Dependent Selection on Warning Color in Alpine Leaf Beetles

Abstract: Müller's theory of warning color and mimicry, despite forming a textbook example of frequency-dependent selection, has rarely been demonstrated in the wild. This may be largely due to the practical and statistical difficulties of measuring natural selection on mobile prey species. Here we demonstrate that this selection acts in alpine beetle communities by using tethered beetles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
73
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 24 publications
(36 reference statements)
2
73
1
Order By: Relevance
“…Experiments in the laboratory (13,14) and in natural contexts (15)(16)(17)(18) have demonstrated that naive predators have the cognitive capabilities to associate conspicuous signals with toxicity, and to avoid them later. Transplant experiments with live prey or artificial prey models performed in the field have shown increased survival for prey matching the locally abundant warning signal and lower fitness for prey with exotic or novel signals, explaining the stable geographic mosaic of locally uniform warning signals observed (16,17,(19)(20)(21).However, selection favoring mimicry in those studies takes on the pattern of purifying selection for local signals (15,17,20), so the role of positive FDS in the evolution of mimicry is unclear. Indeed, distinguishing the effect of positive FDS from local purifying selection is particularly challenging because the polymorphism necessary to distinguish between them is intrinsically unstable when the most common forms are favored (15-17, 20, 22).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Experiments in the laboratory (13,14) and in natural contexts (15)(16)(17)(18) have demonstrated that naive predators have the cognitive capabilities to associate conspicuous signals with toxicity, and to avoid them later. Transplant experiments with live prey or artificial prey models performed in the field have shown increased survival for prey matching the locally abundant warning signal and lower fitness for prey with exotic or novel signals, explaining the stable geographic mosaic of locally uniform warning signals observed (16,17,(19)(20)(21).However, selection favoring mimicry in those studies takes on the pattern of purifying selection for local signals (15,17,20), so the role of positive FDS in the evolution of mimicry is unclear. Indeed, distinguishing the effect of positive FDS from local purifying selection is particularly challenging because the polymorphism necessary to distinguish between them is intrinsically unstable when the most common forms are favored (15-17, 20, 22).…”
mentioning
confidence: 96%
“…Experiments in the laboratory (13,14) and in natural contexts (15)(16)(17)(18) have demonstrated that naive predators have the cognitive capabilities to associate conspicuous signals with toxicity, and to avoid them later. Transplant experiments with live prey or artificial prey models performed in the field have shown increased survival for prey matching the locally abundant warning signal and lower fitness for prey with exotic or novel signals, explaining the stable geographic mosaic of locally uniform warning signals observed (16,17,(19)(20)(21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The potential that the many migratory species of birds that visit northerly areas widely generalize their avoidance of aposematic taxa by general cues also exists (i.e., avoiding anything with bright conspicuous colors or patterns). Some work on alpine borer beetles in Europe has shown evidence of positive FDS (Borer et al 2010), but work on the wood tiger moth has not (Nokelainen 2013, Hegna et al 2013a). …”
Section: Frequency-dependent Selectionmentioning
confidence: 99%
“…Some of the species found to have geographically varying warning signals include Neotropical Heliconius butterflies (Brown & Benson 1974, Brower 1996, Mallet 2010, ladybird beetles (Creed 1966, Brakefield 1985, Dolenská et al 2009, Blount et al 2012, monarch butterflies (Brower 1958, Davis et al 2005, Davis et al 2012, newts (Mochida 2009, Mochida 2011, poison frogs (Daly & Myers 1967, Savage 1968, Summers et al 2003, Wang & Summers 2010, Wang 2011, Rudh et al 2011, Maan & Cummings 2012, Willink et al 2013, RichardsZawacki et al 2013, Hegna et al 2013b), velvet ants (Wilson et al 2012), alpine leaf beetles (Borer et al 2010), and bumble bees (Plowright & Owen 1980). Interestingly, some aposematic species appear to switch between aposematic and cryptic strategies across their distributions.…”
Section: Geographic Variation For Different Preymentioning
confidence: 99%